1998
DOI: 10.1103/physrevb.57.10923
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of polycrystallineYBa2Cu4O8

Abstract: The thermal conductivity and electrical resistivity were measured on two samples of the cuprate superconductor YBa 2 Cu 4 O 8 ͑Y124͒. The results pass through a maximum at about half of the superconducting transition temperature T c . The peak value is much higher than the peak value for polycrystalline YBa 2 Cu 3 O 7Ϫ␦ , Y123, and is about equal to ab plane values for good melt processed Y123. In the normal state most of the is due to phonon transport p and estimates of p were obtained from the data by making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Electronic component of thermal conductivity in HT c superconductors was calculated with different models by some groups. Williams et al found that the electronic part of j(T) of YBCO was about 30% of the measured room-temperature j(T) value [47]. On the other study, Krishana et all found that the electronic j(T) at T > T c in optimally doped single-crystal Y-123 represented only 10% of the total j(T) [48].…”
Section: Thermal Conductivity Analysismentioning
confidence: 94%
“…Electronic component of thermal conductivity in HT c superconductors was calculated with different models by some groups. Williams et al found that the electronic part of j(T) of YBCO was about 30% of the measured room-temperature j(T) value [47]. On the other study, Krishana et all found that the electronic j(T) at T > T c in optimally doped single-crystal Y-123 represented only 10% of the total j(T) [48].…”
Section: Thermal Conductivity Analysismentioning
confidence: 94%
“…There have been several studies investigating the temperature dependence of the lattice properties [1][2][3], optical properties [4,5] and, thermal properties [6][7][8][9][10][11][12][13] of YBa 2 Cu 3 O 7−x and YBCO/substrate boundary resistance [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The resistivity increases as the doping decreases from the Fermi liquid into the pseudogap region. Moreover, the thermal conductivity κ, 51,52 the thermopower S 53,54 and the tunneling conductance g 55 have been investigated near the quantum critical point of the cuprates. κ is observed to be nearly independent of temperature in the marginal Fermi liquid state 56 and depends on 1/T in the Fermi liquid region.…”
mentioning
confidence: 99%